Age and Gender Predilection of Oral Submucous Fibrosis in An Outpatient Population of a Dental College- A Retrospective Study - THIRUMAGAL, K.; S, GHEENA.; JAIN, RAVINDRA KUMAR (The journal of contemporary issues in business and government, 2021)
Oral sub mucous fibrosis (OSMF) is an oral precancerous condition. It is a chronic debilitating and crippling condition of the oral mucosa classified as a potentially malignant disorder. The inflammation and the progression of fibrosis will result in rigidity and trismus. The etiology of OSMF includes tobacco, areca nut chewing, excessive use of chillies and lime in diet, immunological disorders, collagen disorder and nutritional deficiencies. The symptoms are trismus that is reduced mouth opening, oral pain, burning sensation, hearing loss and change of gustatory sensation. A retrospective study was planned with data collection from June 2019 to March 2020 in a university setup. We reviewed the patients records and analysed the data of 86000 patients.The data report includes patient details like gender, age and diagnosis. The records were manually verified by 2 reviewers and the data was tabulated in the Excel sheet followed by statistical analysis using SPSS software (Statistical Product and Service Solutions) in IBM and chi-square tests were performed. Total subject population was 191 in the age range of 11-70 years, males with OSMF were 86(45.0%) and females with OSMF were 7 (3.6%),the majority of patients 26(13.6%) with OSMF were in the 31-40 years age grp. Within the limitations of the study, it can be concluded that male have higher predilection to OSMF when compared with females and the most common age group affected by OSMF was in the age range of (31-40) years.